STORY-TELLING IN JUDICIAL DISCOURSE - SMEJKALOVÁ, Terezie (Comparative Legilinguistics, 2017)
Judicial discourse and the style of written judicial decisions has been subject of numerous analyses. Judicial discourse comprises different elements from formal and structural ones to various modes of argumentation used. Narrative – when approached as a form or a structure – may be helpful in thorough analyses of judicial discourse, in particular the texts of judgements. This paper analyzes one judgement of a Czech court by means of narrative analysis and tackles the issues of narrative differentiation, narrative structure and narrative coherence in relation to judicial decision-making. Furthermore, it addresses the issue of story-telling and its importance within judicial discourse.